Ecoenzyme Production, Characteristics and Applications: A Review - Gumilar, Gun Gun; Kadarohman, Asep; Nahadi, Nahadi (Jurnal Kartika Kimia, 2023)
The reuse and management of organic waste can reduce significantly the impact on the environment and human health, as well as improve economic value through developing value-added products of certain applications. One of the solutions to cut down is solid organic waste such as fruit and vegetable waste into ecoenzymes via fermentation. This current review discusses the production, characterization, and application of ecoenzymes. The data was gathered from international and national indexed journals and proceedings. Ecoenzyme is produced via fermentation from fruit/vegetable waste, sugar, and water with a ratio of 1:3:10. In general, the modification made is changing the type of sugar and the type of fruit/vegetable waste used as raw material. The characterization mainly focuses on evaluating the content and activity of the enzymes. Wide range of applications of ecoenzyme found as liquid fertilizers, antimicrobial agents, wastewater treatment processes, and sludge treatment processes.